2021
DOI: 10.3390/microorganisms9071477
|View full text |Cite
|
Sign up to set email alerts
|

Common and Rare Hematological Manifestations and Adverse Drug Events during Treatment of Active TB: A State of Art

Abstract: Background: Tuberculosis (TB) can seriously affect the hematopoietic system, with involvement of both myeloid and lymphoid cell lines as well as plasma components. These hematological changes act as a marker for the diagnosis, prognosis and response to therapy. Methods: We searched PubMed, Scopus, Google Scholar, EMBASE, Cochrane Library and WHO websites from 1950 to May 2021 for papers on the interaction between TB and common and rare hematological manifestation. Results: Hematological reactions in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 89 publications
0
22
0
4
Order By: Relevance
“…However, it is unclear whether VD deficiency is a possible cause or consequence of the disease. Numerous in vitro studies have demonstrated the role and potential benefit of VD in TB, showing that VD suppresses the replication of MTB in vitro [ 82 , 83 ]; few clinical trials have been performed to evaluate the efficacy of VD supplementation in preventing the development of the disease, failing to show a reduction in the risk of infection and development of disease [ 84 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is unclear whether VD deficiency is a possible cause or consequence of the disease. Numerous in vitro studies have demonstrated the role and potential benefit of VD in TB, showing that VD suppresses the replication of MTB in vitro [ 82 , 83 ]; few clinical trials have been performed to evaluate the efficacy of VD supplementation in preventing the development of the disease, failing to show a reduction in the risk of infection and development of disease [ 84 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the half-life of 25(OH)D 2 is lower than that of 25(OH)D 3 , due to the lower affinity of the former for VDBP. The half-life of vitamin D is reduced when there are low levels of VDBP, such as in the case of increased loss in nephrotic syndrome [ 12 ]. In the kidney, 25(OH)D is further hydroxylated by an oxidase and then transformed into the active hormone: 1,25 dihydroxy vitamin D [1,25(OH) 2 D] or calcitriol.…”
Section: Metabolism Of Vitamin Dmentioning
confidence: 99%
“…This oxidase is expressed in the cells of the proximal convoluted tubule and subjected to strict regulation: it is stimulated by parathyroid hormone and hypophosphatemia and inhibited by calcium, FGF23 and 1,25(OH) 2 D itself. The active hormone acts on intracellular VDR and influences gene transcription [ 12 , 13 ]. Figure 1 shows metabolism of vitamin D.…”
Section: Metabolism Of Vitamin Dmentioning
confidence: 99%
“…Most patients have low B6 vitamin serum levels. The state is reversible a few weeks after withdrawing the drug or after starting supplementation with pyridoxine [ 70 , 71 ].…”
Section: Non-clonal or Metabolic Acquired Sideroblastic Anemiasmentioning
confidence: 99%